Enabling Mobile Micro-Interactions with Physiological Computing - Tan, Desney; Morris, Dan; Saponas, Scott ((2010) ACM XRDS, 2010)
We have continually evolved computing to not only be more efficient, but also more accessible, more of the time (and place), and to more people. We have progressed from batch computing with punch cards, to interactive command line systems, to mouse-based graphical user interfaces, and more recently to mobile computing. Each of these paradigm shifts has drastically changed the way we use technology for work and life, often in unpredictable and profound ways.